Evaluasi Implementasi Kebijakan Moneter dan Strategi Adaptasi Menghadapi Tantangan Global - Fany Raditya Rahayu; Na’ilatul Fitri Nita Abidah; Rini Puji Astuti (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to evaluate the implementation of Bank Indonesia's monetary policy and the adaptation strategy applied in facing increasingly complex global challenges. Using a qualitative approach through analysis of policy documents, macroeconomic data, and related literature, this study examines the effectiveness of monetary policy in maintaining price stability, exchange rates, and supporting national economic growth. The results of the study indicate that Bank Indonesia has succeeded in maintaining inflation within the target range of 2.5% ± 1% and maintaining the stability of the rupiah exchange rate despite facing external pressures such as the normalization of global monetary policy and geopolitical tensions. However, there are structural challenges such as suboptimal policy transmission and inflation expectations that have not been fully managed. In response, Bank Indonesia developed an adaptation strategy that includes strengthening policy coordination through the Financial System Stability Committee (KSSK). The results of this study confirm that the success of monetary policy in maintaining economic stability is highly dependent on adaptive responses to global dynamics, inter-institutional coordination, and innovative capabilities in designing inclusive and sustainable policy strategies and this study provides important implications for strengthening the framework for adaptive and responsive monetary policy in the future.